South African women's theologies of hope in the new struggle against HIV/AIDS - Williams, Kim (University of Cape Town, 2006)
South Africa has been hard hit by the HIV/AIDS pandemic. This pandemic has had many sectors in society mobilizing and creating awareness around prevention and the effects of HIV/AIDS. One such sector is the religious community, which, with all its diversity, has tried to address the issues that stem from this pandemic. This mmor dissertation looks at the South African situation of HIV I AIDS from a gendered religious perspective, the perspective of South African Christian women's theologies. It further catalogs the research to Anglican women in Cape Town. This study aims to find the participatory levels and status of Christian Anglican women in the church's mobilization activities and decision making. Through this study two main theologies are explored, African women's theology and the theology of Hope.
Free